Development of Mobile Android-Based Tracer Study to Improve Graduate Quality in Creating an Independent Campus at Serambi Mekkah University - Susmanto Susmanto; Munawir Munawir; Samsuddin Samsuddin (Universitas Serambi Mekkah, 2022)
Tracer Study is a service provided by higher education institutions to track alumni who have graduated, which can later be used as an assessment. Accreditation of graduates aims to determine educational output in the form of a transition from the world of education to the world of work. Dikti is currently pioneering the complications of the National tracer study data, especially regarding the transition and job position of university graduates in Indonesia. Tracer study at the University of Serambi Mekkah is considered important because it becomes a tool for evaluating the performance of higher education institutions and becomes an assessment by the National Accreditation Board for Higher Education (BAN-PT). The online tracer study has been implemented by Dikti since 2011, but not all universities have conducted an online tracer study system. The Tracer Study of the University of Serambi Mekkah is intended to trace the traces of graduates / alumni carried out 2 years after graduation and aims to find out, educational outcomes in the form of the first job search process, last work situation and application of competencies in the world of work in accordance with the skill areas that have been obtained, output of education is self-assessment of mastery and acquisition of competence, educational process in the form of evaluation of the learning process and the contribution of higher education to the acquisition of competence. Alumni tracking has been carried out by universities through a website-based application at http://tracerstudy.serambimekkah.ac.id. The purpose of this study from the observations that it still has many shortcomings including, the use of functions in the application has not run well as a graduate user and as a solution in this study developing an Android-based Mobile application. The method in this study uses the Software Development Lifecycle (SDLC) which is written on the development of the website system to the mobile application. By using firebase and android platform, It is hoped that the development of mobile-based applications can make it easier for graduate users to fill I tracer study data. Then the results of functionality and compatibility testing generated by tracer study users. An easy data entry process and a familiar interface will determine the quality and quantity of alumni, and make it easier for the faculty or study program level to determine policies in order to improve the quality of graduates, quality of education and accreditation. The convenience of alumni in accessing applications on the Google Playstore will make it easier for alumni to download and install the tracer study application on their cellphones. Keywords: Tracer Study, Android Mobile, Merdeka Campus